2019
DOI: 10.3389/fpls.2019.00808
|View full text |Cite
|
Sign up to set email alerts
|

GmEXLB1, a Soybean Expansin-Like B Gene, Alters Root Architecture to Improve Phosphorus Acquisition in Arabidopsis

Abstract: Expansins comprise four subfamilies, α-expansin (EXPA), β-expansin (EXPB), expansin-like A (EXLA), and expansin-like B (EXLB), which are involved in the regulation of root development and growth under abiotic stress. To date, few EXLB genes have been shown to respond to low phosphorus (P) in plants. In this study, we identified an EXLB gene, GmEXLB1 , by analyzing the transcription profiles of GmEXLBs in soybean. Quantitative analysis showed that GmEXLB1 was expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…Expansins consist of four subfamilies, including α-expansin (EXPA), expansin-like A (EXLA), β-expansin (EXPB) and expansin-like B (EXLB) [52]. To data, three expansin members have been implicated in regulating root architecture and morphology when plants subjected to P deficiency, such as TaEXPB23 from wheat [53], GmEXPB2 and GmEXLB1 from soybean [34,54]. In this study, the expressions of SgEXPB2 and SgEXLB1, the homologies of GmEXPB2 and GmEXLB1, were increased by Pi starvation in roots ( Fig.…”
Section: Modification Of Stylo Root Morphology In Response To Low Pi mentioning
confidence: 99%
See 1 more Smart Citation
“…Expansins consist of four subfamilies, including α-expansin (EXPA), expansin-like A (EXLA), β-expansin (EXPB) and expansin-like B (EXLB) [52]. To data, three expansin members have been implicated in regulating root architecture and morphology when plants subjected to P deficiency, such as TaEXPB23 from wheat [53], GmEXPB2 and GmEXLB1 from soybean [34,54]. In this study, the expressions of SgEXPB2 and SgEXLB1, the homologies of GmEXPB2 and GmEXLB1, were increased by Pi starvation in roots ( Fig.…”
Section: Modification Of Stylo Root Morphology In Response To Low Pi mentioning
confidence: 99%
“…For example, expansins are superfamily proteins that modify cell wall loosening, leading to cell extension [33]. GmEXLB1, one of Pi starvation-inducible expansin genes, identified by transcriptomic analysis in soybean (Glycine max), has been characterized to be involved in P acquisition by regulating root growth [34]. Recently,…”
mentioning
confidence: 99%
“…BrEXLB1 overexpression is consistent with the increase in the size of the elongation zone, thus confirming its role in cell elongation and/or root growth. Previously, Kong et al [27] suggested that soybean EXLB1 may be associated with lateral root emergence. Therefore, we also investigated the BrEXLB1 association with lateral root development by expression profiling of known lateral root marker genes such as GATA23 and MAKR4 genes in OX and OX-AS lines ( Figure S4) and also comparing the lateral root phenotypes.…”
Section: Overexpression Of Brexlb1 Is Positively Associated With the mentioning
confidence: 99%
“…Expansins consist of four subfamilies, including α-expansin (EXPA), expansin-like A (EXLA), β-expansin (EXPB) and expansin-like B (EXLB) [53]. To data, three expansin members have been implicated in regulating root architecture and morphology when plants subjected to P deficiency, such as TaEXPB23 from wheat [54], GmEXPB2 and GmEXLB1 from soybean [34,55]. In this study, the expressions of SgEXPB2 and SgEXLB1, the homologies of GmEXPB2 and GmEXLB1, were increased by Pi starvation in roots ( Fig.…”
Section: Modification Of Stylo Root Morphology In Response To Low Pi mentioning
confidence: 99%
“…For example, expansins are superfamily proteins that modify cell wall loosening, leading to cell extension [33]. GmEXLB1, one of Pi starvation-inducible expansin genes, identified by transcriptomic analysis in soybean (Glycine max), has been characterized to be involved in P acquisition by regulating root growth [34]. Recently, a pair of rice vacuolar Pi efflux transporters (OsVPE1 and OsVPE2) identified by vacuolar membrane proteomics, have been demonstrated to participate in vacuole Pi remobilization [35].…”
Section: Introductionmentioning
confidence: 99%